Implementasi Data Mining dalam Clustering Menu Favorit Pada Cafe Anetos.Coffeebrunch Menggunakan Algoritme K-Means - Widodo, Rizky Andaru; Jananto, Arief (Progresif: Jurnal Ilmiah Komputer, 2023)
Cafe Anetos.Coffeebrunch is a cafe business engaged in the culinary field. With the growth of the food and beverage business, there will be competition in the business at each café, so that Café Anetos.Coffeebrunch will be able to compete by using sales transaction data at Cafe Anetos.Coffebrunch to be able to plan and create/determine sales strategies. By using data mining to define a sales strategy in order to be able to identify which products need to be improved and actually want to provide decision-making problem solving. The procedure here uses a clustering procedure using the k-means algorithm. With this, using the Rstudio tools, we obtained 3 clusters, namely for cluster 1 with the highest score found in Anetos Ice Milk Coffee with a total of 277 purchases. Cluster 2 has the highest score for Yakult Lychee Tea Ice with a total of 127 purchases. In cluster 3 which has the highest value is Lychee Tea Ice with a total of 427 purchases. This result will in fact be able to increase sales and stock management at Café Anetos. Coffee breakfast.Keywords: Café Business; Classification; K-Means Clustering; Sales Strategy AbstrakCafe Anetos.Coffebrunch merupakan usaha cafe yang bergerak dibidang kuliner. Dengan pertumbuhan bisnis food and beverage hendak terdapatnya persaingan dalam bisnis di tiap café, hingga dari itu Café Anetos.Coffebrunch wajib sanggup bersaing dengan menggunakan data transaksi penjualan pada Cafe Anetos.Coffebrunch buat dapat memplanning serta membuat/ memastikan strategi penjualan. Dengan memakai data mining buat memastikan strategi penjualan supaya bisa mengenali produk mana yang wajib ditingkatkan serta nyatanya hendak membagikan pemecahan soal pengambilan keputusan. Tata cara disini memakai tata cara clustering dengan menggenakan algoritme K-means. Dengan ini memakai tools Rstudio memperoleh hasil 3 kluster ialah Buat kluster 1 dengan nilai paling tinggi terdapat pada Kopi Susu Anetos Ice dengan total 277 pembelian. Klaster 2 nilai paling tinggi terdapat pada Yakult Lychee Tea Ice dengan total 127 pembelian. Pada kluster 3 yang mempunyai nilai paling tinggi merupakan Lychee Tea Ice dengan total 427 pembelian. Hasil ini nyatanya hendak bisa tingkatkan penjualan serta manajemen stok di Café Anetos. Coffebrunch.Kata kunci: Usaha Café; Pengelompokan; K-Means Klastering; Strategi Penjualan